Preparation and Characterization of porous tubular scaffold made of PCL/PLCL blends for vascular tissue engineering / Azizah Pangesty and Mitsugu Todo - Pangesty, Azizah; Todo, Mitsugu (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Porous tubular scaffolds had been developed by physically blending poly-ε-caprolactone (PCL) and poly-(lactide-co-ε-caprolactone) (PLCL) using solid-liquid phase separation method subsequent with freeze-drying method. The effect of blending ratio on the morphology and mechanical properties of PCL/PLCL blends tubular scaffold had been investigated. The blending were confirmed using infrared spectroscopy. The microstructure behaviour were observed using scanning electron microscopy and the mechanical properties were evaluated using ring tensile test. It was concluded that the resulted tubular scaffold possessed an improved elastic modulus and enlarged pore size as the content of PLCL increased. The tubular scaffold containing 75% PLCL was found as the optimum blends ratio in terms of elastic modulus and rebound properties. The tubular scaffold made of PCL/PLCL blends has a potential for vascular tissue engineering application.